“General (Who Is) Above the Four Generals” in the Seleucid and Arsacid Periods - Mitsuma, Yasuyuki (Anabasis. Studia Classica et Orientalia, 2019)
In this paper, we will discuss the status and character of the “general above the four generals” based on the entries in Late Babylonian Astronomical Diaries and Babylonian Chronicles of the Hellenistic Period. For clarifying the relationship of the office and “Upper Satrapies” in the Seleucid Empire, we will determine its geographical expanse in Section 2 and argue that the western border of the “Upper Satrapies” was the Euphrates, and the city of Babylon and Babylonia was included in the “Upper Satrapies”. In Sections 3, we will discuss the status of the Seleucid dignitaries mentioned as “general above the four generals” on the basis of the entries shown in Table 1 (nos. 1–10), and reconfirm that the office referred to as “general above the four generals” corresponds to the governor-general of the “Upper Satrapies,” or “one who is above the Upper Satrapies” in Greek inscriptions. In Section 4, we will use the entries collected in Table 1 (nos. 11–47) from the Arsacid Diaries and Chronicles and clarify the status and character of the “general above the four generals” or “one who is above the Upper Satrapies” after the Arsacid takeover of Babylonia (141/140 BC).